Gifts of the Muse: Reframing the Debate about the Benefits of the Arts - McCarthy, Kevin F. (RAND Corporation, 2004)
During the past decade, arts advocates have relied on an instrumental approach to the benefits of the arts in arguing for support of the arts. This report evaluates these arguments and asserts that a new approach is needed. This new approach offers a more comprehensive view of how the arts create private and public value, underscores the importance of the artsÂ' intrinsic benefits, and links the creation of benefits to arts involvement.